Polylog of root of unity

Calculus Level 5

k = 1 n Li 2 ( ω k x ) = f ( n ) Li 2 ( x ) + g ( n ) Li 2 ( x n ) \large \sum_{k=1}^n \text{Li}_2(\omega^k x)=f(n)\text{Li}_2(x)+g(n)\text{Li}_2(x^n)

The equation above holds true for rational functions f f and g g and ω \omega is the primitive n th n^\text{th} roots of unity for integer n > 1 n>1 . Find ( f + g ) ( 1 ) (f+g)(1) .

Notation : Li n ( a ) { \text{Li} }_{ n }(a) denotes the polylogarithm function, Li n ( a ) = k = 1 a k k n . { \text{Li} }_{ n }(a)=\displaystyle\sum _{ k=1 }^{ \infty }{ \frac { { a }^{ k } }{ { k }^{ n } } }.


The answer is 1.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Julian Poon
Mar 23, 2016

Lemma:

k = 1 n m = 1 ω k m f m = n m = 1 f n m \sum _{k=1}^n\sum _{m=1}^{\infty} \omega^{km}f_m=n\sum _{m=1}^{\infty}f_{nm}

Proof:

Rearranging the terms give

k = 1 n m = 1 ω k m f m = m = 1 k = 1 n f m ω k m = m = 1 f m k = 1 n ω k m \sum _{k=1}^n\sum _{m=1}^{\infty} \omega^{km}f_m=\sum _{m=1}^{\infty}\sum _{k=1}^nf_m\omega^{km}=\sum _{m=1}^{\infty}f_m\sum _{k=1}^n\omega^{km}

k = 1 n ω k m = ω 1 ω k 1 ω = { n if k is a multiple of n 0 otherwise \sum _{k=1}^n\omega ^{km}=\omega \frac{1-\omega ^k}{1-\omega }=\begin{cases}n \text{ if } k \text{ is a multiple of }n\\0 \text{ otherwise}\end{cases}

Hence

m = 1 f m k = 1 n ω k m = m = 1 n f n m = n m = 1 f n m \sum _{m=1}^{\infty}f_m\sum _{k=1}^n\omega^{km}=\sum_{m=1}^{\infty}nf_{nm}=n\sum_{m=1}^{\infty}f_{nm}


Now for the question, we want to find

k = 1 n m = 1 ω k m x m m 2 \sum _{k=1}^n\sum _{m=1}^{\infty}\frac{\omega ^{km}x^m}{m^2}

So, making f m = x m m 2 f_m=\frac{x^m}{m^2} gives

k = 1 n m = 1 ω k m x m m 2 = n m = 1 x m n ( m n ) 2 = n 1 Li 2 ( x n ) \sum _{k=1}^n\sum _{m=1}^{\infty}\frac{\omega ^{km}x^m}{m^2}=n\sum_{m=1}^{\infty}\frac{x^{mn}}{(mn)^2}=n^{-1}\text{Li}_2(x^n)

The answer follows

Extra

Otto Bretscher
Mar 23, 2016

Let's compare the derivatives of both sides, with the derivative of the LHS being ln ( 1 ω k x ) x -\sum\frac{\ln(1-\omega^kx)}{x} .

Now d d x ( L i 2 ( x n ) ) = n ln ( 1 x n ) x = n ln ( ( 1 ω k x ) ) x = n ln ( 1 ω k x ) x \frac{d}{dx}\left(Li_2(x^n)\right)=-\frac{n\ln(1-x^n)}{x}=-\frac{n\ln(\prod(1-\omega^kx))}{x}=-n\sum\frac{\ln(1-\omega^kx)}{x}

It follows that f ( n ) = 0 f(n)=0 and g ( n ) = 1 n g(n)=\frac{1}{n} , so that the answer is 1 \boxed{1}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...